An assessment of the EU proposal for ceilings on the use of Kyoto flexibility mechanisms - Zhong Xiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2000)
The Kyoto Protocol is the first international environmental agreement that sets legally binding greenhouse gas emissions targets and timetables for Annex I countries. It incorporates emissions trading, joint implementation and the clean development mechanism. Because each of the Articles defining the three flexibility mechanisms carries wording that the use of the mechanism must be supplemental to domestic actions, the supplementarity provisions have been the focus of the international climate change negotiations subsequent to Kyoto. Whether the supplementarity clauses will be translated into a concrete ceiling, and if so, how should a concrete ceiling on the use of the three flexible mechanisms be defined remain to be determined. To date, the European Union (EU) has tabled a proposal for ceilings on the use of these flexibility mechanisms. Given the great policy relevance to the ongoing negotiations on the overall issues of flexibility mechanisms, this paper has provided a quantitative assessment of the implications of the EU ceilings with and without considering the however clause. Our results suggest that such ceilings are less restrictive to the EU than to the US and Japan in terms of levels of restriction on permits imports, and can prevent one third of the amount of hot air from entering the market. Our results also demonstrate that although the US and Japan are firmly opposed to such a restriction, they tend to benefit more from it than the EU which strongly advocates such ceilings, in terms of the reductions in the total abatement costs relative to the no trading case. Moreover, their gains can increase even further, provided that the however clause would operate as intended.
Keywords: Q28; Q25; Q48; Q43; 330; Emissions trading; clean development mechanism; joint implementation; greenhouse gases; European Union; supplementarity restrictions